2012
DOI: 10.1177/0022022112466699
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation Expectations and Experiences as Predictors of Ethnic Migrants’ Psychological Well-Being

Abstract: There is a need for a better acknowledgement of the pre-and postmigration factors that influence postmigration psychological adaptation of ethnic migrants. In the present study, first, we examined the effects of pre-acculturative stress, anticipated sociocultural difficulties, and anticipated discrimination on ethnic migrants' (N = 153) psychological well-being in the postmigration stage. These pre-migration factors were expected to influence postmigration acculturation experiences (i.e., perceived acculturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 74 publications
(122 reference statements)
2
25
1
Order By: Relevance
“…Life Satisfaction increased and Self‐Esteem decreased. These changes in opposite directions could explain why our previous study, Mähönen & Jasinskaja‐Lahti (), which employed the broad bandwidth General Well‐Being Index (Gaston & Vogl, ), found no changes in well‐being before and after migration. Our result could be considered unexpected because Self‐Esteem has in cross‐sectional research been considered one of the main determinants of Life Satisfaction (e.g., Campbell, ; Diener & Diener, ; Kwan, Bond, & Singelis, ).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Life Satisfaction increased and Self‐Esteem decreased. These changes in opposite directions could explain why our previous study, Mähönen & Jasinskaja‐Lahti (), which employed the broad bandwidth General Well‐Being Index (Gaston & Vogl, ), found no changes in well‐being before and after migration. Our result could be considered unexpected because Self‐Esteem has in cross‐sectional research been considered one of the main determinants of Life Satisfaction (e.g., Campbell, ; Diener & Diener, ; Kwan, Bond, & Singelis, ).…”
Section: Discussionmentioning
confidence: 75%
“…Third, perceived everyday difficulties, including experiences of difficult intergroup relations, are also factors likely to have a strong impact on migrants' well‐being. A previous study (Mähönen & Jasinskaja‐Lahti, ) using the same sample of Ingrian Finns—but only one post‐migration assessment and a different measure of well‐being—showed that difficulties in socio‐cultural adaptation (Brisset, Safdar, Lewis, & Sabatier, ), acculturative stress (Lazarus & Folkman, ), and experiences of discrimination (Berry et al, ; Jasinskaja‐Lahti et al, ) are all relevant in predicting migrants' well‐being. All of these factors are widely studied precursors of immigrant adaptation (Berry, ).…”
Section: Life Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Varjonen, Arnold, & Jasinskaja-Lahti, 2013). 1 Although ethnic migrants often face rejection and questioning of their identity, their identification with host nationals is typically high, and being treated as a full member of the society is typically expected (Mähönen & Jasinskaja-Lahti, 2013;Tartakovsky, 2008). Also, because of their preparations before migration (e.g.…”
mentioning
confidence: 99%